The Digital Role in Building Public Profiles of Political Actors - Punziano, Gabriella; Esposito, Federico; Padricelli, Giuseppe Michele (Italian Sociological Review, 2022)
In the middle of an era characterized by continuous electoral campaigns and by the personalization of politics contained in the better-known platform society, our paper aims to shed light on the planning dynamics and practices carried out inside and outside the Net by those political actors in charge of the local election arena. Which factors related to political networks push individuals to run for a political position? What are the biographies, cultural and local relations of the territories they run for? What are the differences between political competitors in terms of the digital competence needed for campaign communication and promotion? The research design focuses on a specific case study shaped on the last local election in Naples. Through the study of the political biographies of the candidates, a framework analysis was conducted on press releases, aiming to understand the inferred narration of the election and a content analysis conducted on their official social media sources to comprehend the self-building political narratives of the observed candidates. This study aims to create a clear categorization of candidates, to understand the current digital customs adopted by political actors to draw and define their own political strategies.